Building Android apps with HTML, CSS, and JavaScript - Stark, Jonathan, 1968- (O'Reilly, 2012)
If you know HTML, CSS, and JavaScript, you already have the tools you need to develop Android applications. Now updated for HTML5, the second edition of this hands-on guide shows you how to use open source web standards to design and build apps that can be adapted for any Android device. You'll learn how to create an Android-friendly web app on the platform of your choice, and then use Adobe's free PhoneGap framework to convert it to a native Android app. Discover why device-agnostic mobile apps are the wave of the future, and start building apps that offer greater flexibility and a much broader reach. Convert a website into a web application, complete with progress indicators and other features Add animation with JQTouch to make your web app look and feel like a native Android app Make use of client-side data storage with apps that run when the Android device is offline Use PhoneGap to hook into advanced Android features, including the accelerometer, geolocation, and alerts Test and debug your app on the Web with real users, and submit the finished product to the Android Market.